Masa ‘Iddah Bagi Perempuan Mustaḥaḍah Mutaḥayyirah Dalam Perspektif Mażhab Maliki dan Mażhab Syafi’i - Mustakim, Ahmad; Musyafa’, Muhammad Anton (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2025)
‘Iddah is one of the Islamic laws that must be carried out by Muslim women who lose their marital status for certain reasons. Problems arise when the women undergoing the ‘iddah period are women who are mustaḥaḍah mutaḥayyirah, namely women who are unable to differentiate between ḥaiḍ blood and istiḥāḍah blood. Departing from this problem, this study was conducted to examine and determine the ‘iddah period that must be carried out by women who are mustaḥaḍah mutaḥayyirah based on the perspectives of the Maliki and Shafi’i schools of thought, and to compare the opinions of the two schools of thought to find points of difference between them. According to the Imam Maliki Mażhab, the period of 'iddah for mustaḥaḍah mutaḥayyirah women is one year, with a breakdown of nine months to eliminate doubts and ensure the emptiness of the womb, as well as three months as a period of 'iddah equal to women in general, as a form of iḥtiyāṭ (prudence). Meanwhile, the Syafi'i Mażhab believes that the 'iddah period is sufficient for three months, because women essentially experience ḥaiḍ and become pure periodically, and extending the 'iddah period is considered to give rise to masyaqqah. The difference between these two schools of thought lies in determining the duration of the ‘iddah period and the method of istinbāṭ law. The Maliki school uses qawl ṣaḥābah and maṣlaḥah mursalah, while the Shafi’i school bases its opinion on the Qur’an, Hadith, and Qiyās.